Developmental and behavioral outcomes of uncomplicated monochorionic diamniotic twins born in the third trimester - Sierakowski A (Dove Medical Press, 2017)
Amy Sierakowski,1 Valsamma Eapen,2,3 Rudi Črnčec,2,3 John Smoleniec4,5 1University of New South Wales, 2School of Psychiatry, University of New South Wales, 3Academic Unit of Infant, Child and Adolescent Psychiatry, Ingham Institute, Liverpool Hospital, South Western Sydney Local Health District, 4Division of Women’s and Children’s Health, University of New South Wales, Sydney, 5Department of Maternal-Fetal Medicine, Liverpool Hospital, Liverpool, NSW, Australia Background: Relatively little is known about the neurodevelopmental and behavioral outcomes of monochorionic diamniotic (MCDA) twin pregnancies where there are no antenatal complications peculiar to monochorionicity or prematurity.Methods: Twenty-two MCDA twins (44 children) with an average age of 4.3 years, and with no antenatal complications detected by 28 weeks of gestation, were recruited from a feto-maternal unit database. Parents completed a battery of neurodevelopmental and behavioral assessment questionnaires.Results: Eighteen children (41%) were identified as having developmental or behavioral concerns, predominantly of mild severity, which in turn were associated with a lower birth weight of medium effect size (Cohen’s d=0.59).Conclusion: MCDA twins delivered in the third trimester with no antenatal monochorionic complications in the first two trimesters appear to be at risk for subtle neurodevelopmental difficulties, associated with a lower birth weight. Ongoing developmental surveillance of these children during preschool-age is indicated for early identification and intervention. Keywords: monochorionic, diamniotic, twin, neurodevelopment, behavior, long-term outcome